Cribra orbitalia and Porotic hyperostosis on bone remains of the Bronze Age population from the Lower Volga region (search for the proliferation causes) - Pererva E.V. (Вестник археологии, антропологии и этнографии)
This study is devoted to defining the occurrence frequency of Cribra orbitalia and Porotic hyperostosis signs based on the data obtained and establishing the reasons for the spread of these pathological conditions in the study groups. The material for the study is series dating back to the Early, Middle and Late Bronze Ages from the Lower Volga region kurgan mounds. When analyzing bone remains, the occurrence of porotic hyperostosis on the skull and cribra orbitalia was taken into account. To identify significantly significant differences in the incidence of pathological abnormalities, the groups were compared using non-parametric mathematical criteria. Statistical calculations were carried out in the StatSoft, Inc. shell. (2011) STATISTICA. As a result of the study, it was established that the factors influencing the occurrence of signs of hemolytic diseases in the study group could be endemic malaria, helminths, as well as nutritional stress caused by systematic starvation, lack of vitamin C, folic acid, cobalamin and iron.